(untitled) (Revista Eletrônica Debates em Educação Científica e Tecnológica, 2026)
The teaching of evolution is approached in a fragmented way, with emphasis on memorizing concepts presented in a decontextualized way. An alternative to provide a more coherent learning of evolutionary biology content would be the use of phylogenetic systematics. For Vygotsky (1989), the learning process takes place in a complex way, covering different fields, such as cognitive, emotional and social. An alternative to contextualized and dynamic teaching is the use of playful teaching resources. We believe that the development of teaching-learning of evolutionary concepts can be better explored by contextualizing them with elements of phylogeny in the application of didactic sequences that include playful approaches. Therefore, the objective of this work was to evaluate the conceptual development of Evolution in third-year high school students at the Federal Institute of Maranhão (IFMA), Caxias campus, in the city of Caxias-MA, based on the application of a didactic sequence with the game Cladeway. The research sought to deepen the understanding of complex evolutionary concepts. Through a qualitative empirical-experimental approach. The students were divided into two groups, experimental and control groups. Both groups participated in a didactic sequence with theoretical classes and pre- and post-test questionnaires, but only the experimental group participated in the application of the CladeWay game. The results indicated that the experimental group better understood evolution and phylogenetic systematics, highlighting the effectiveness of this playful approach. We conclude that in addition to theoretical classes, alternative methods such as games can overcome individual challenges, boosting engagement and practical application of knowledge.